INTEGRATING READING AND WRITING IN ACADEMIC WRITING CLASS - Fernandita Gusweni Jayanti (Indonesian JELT, 2013)
Based on the theories and empirical data of the advantages oforchestrating integrated skills in the classroom and the connectionsbetween reading and writing skill, this study aims to find out theeffects of integrated reading-writing instruction on students’writing ability. The moderating effect of cognitive styles was alsoinvestigated. The present study adopted a quasi-experimentaldesign with 2 x 2 factorial analyses. The subjects of this studywere 87 students at STKIP PGRI Jombang. An experimental groupusing integrated reading-writing instruction was randomlyassigned for comparison with a group using a traditional teachingmodel. At first, the participants were asked to perform GroupEmbedded Figure Test (GEFT) to determine their cognitive styles.After that, the participants were asked to write an expository essayas the pre-test to justify that both groups had the same writingability before the treatment. After seven meetings of treatment,they were asked to write another expository essay as the post-test.Based on ANOVA analyses, it was found that the students taughtby using integrated reading-writing instruction did not achievesignificantly better writing score than students taught by writinginstruction only: neither for the field-independent students nor thefield-dependent ones.Keywords: integrated reading and writing, writing instruction,writing ability, cognitive styles